(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Using traditional and inactive methods in medical education can cause fatigue, lack of attention, frustration, lack of motivation and decrease the level of students’ learning. games in education is one of the interactive, active and fun methods that has its own educational purpose that translates the special features and highlights the special capabilities by deepening the skills . In this article, the effect of the instructional game as a educational puzzles and the effect of this program on students ‘ self-regulation and team learning has been investigated. Method: This research is a pre test – post test semi experimental study. The population of this study was Jahrom University of Medical Sciences students and samples were 39 nursing students which studied psychiatric course. Sample was selected from available class to the teacher. Initially, the content of the course was presented as a presentation of the main content of the lecture. After the completion of the lessons, contents prepared through puzzle and this program was given to small groups in all sessions. The groups, while answering the questions, checked the collection of information and the searched for the answers, and then the correct answer was provided by the teacher. The combination of teamwork with small groups and solving puzzles which contained learned lessons provided an attractive environment in the form of teamwork. Four questionnaires included : self-directed learning readiness scale (SDLRS), Burrfurd’s self-regulatory questionnaire and a Questionnaire for assessing the value of team work and then a questionnaire of self-reflection were used in two stages (before and after) of intervention. Results: The results of the study showed that self-regulatory indicators (p = 0.17) and self-directed (including self-control motivation) and self-management (p=0.15, p=0.0, p=0.001) were meaningful after improving intervention respectively. Other results show that intervention has affected team-based learning scales (including attitudes- team learning and team-learning skills (0.73, 046, 0.62) although it is not significant. Also, the mean increase in all subdomain of selfreflection were significant (p <0.05). Other results indicated that the intervention increased the mean scores of self-regulation and self-directed of students. But it is only in self-management was significant. Conclusion:The results of the study showed that the use of instructional al game can affect the individual and participation learning by creating entertaining and interactive environment. Therefore, it is recommended that the mentioned method be used in medical science education Bangladesh Journal of Medical Science Vol.17(4) 2018 p.631-637